A person-oriented approach to sport and school burnout in adolescent student-athletes: The role of individual and parental expectations. (January 2017) - Sorkkila, Matilda; Aunola, Kaisa; Ryba, Tatiana V.
Abstract: Objectives: The present study aimed to examine what kind of burnout profiles exist among student-athletes based on their sport and school burnout symptoms. Moreover, it was investigated whether athletes' expectations of success in sport and school, on the one hand, and parental expectations, on the other hand, were predictors of the likelihood of the athlete to show a certain profile, after taking into account the effects of gender, grade point average, type of sport, and level of competition. Design and methods: The participants were 391 student-athletes (51% females) from six different upper secondary sport schools in Finland, and 448 parents (58% mothers). The athletes filled in questionnaires about burnout and success expectations at the beginning of the first year of upper secondary school. At the same time point, parents were asked to answer a questionnaire on their success expectations for their child. Structural equation modeling and latent profile analysis were used to analyze the data. Results: Four burnout profiles were identified: well-functioning, mild sport burnout, school burnout, and severe sport burnout. Athletes' and parents' expectations of success seemed to protect against burnout in the same domain, but this protection did not extend to the other domain. Moreover, high success expectations in one domain seemed to increase the risk for burnout in another domain. Conclusions: Burnout needs to be investigated within and across context in order to gain a holistic understanding of student-athletes' wellbeing. Highlights: Four distinct burnout profiles were identified in student-athletes based on symptoms of sport and school burnout. Athletes' and mothers' success expectations in sport predicted the likelihood to show certain kind of profile. Athletes' and both parents' success expectations in school predicted the likelihood to show certain kind of profile. Success expectations in sport and school seemed to be protective from burnout in the same domain, but not across domain.